Financial constraints and firm exports: Accounting for heterogeneity, self-selection and endogeneity - Angelo Secchi; Federico Tamagni; Chiara Tomasi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2014)
The paper examines the causal effect of financial constraints on firm exports. We exploit a firm-level proxy of constraints based on credit ratings and available for a large panel of Italian exporting and non exporting firms. Our estimation strategy allows to cure for self-selection into exports and endogeneity of financial constraints. At the same time, we can control for unobserved firm fixed effects both in the selection and in the export equation, thus identifying the effect on exports of within firm changes in financial constraints status. We find that financial constraints produce a sizable reduction in the value of firm foreign sales.
Keywords: F10; F14; F36; G20; G32; L25; 330; financial constraints; exports; self-selection; endogeneity